Text-to-Speech Software and Reading Comprehension: The Impact for Students with Learning Disabilities - Raffoul, Sandra; Jaber, Lindsey (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
This literature review examines the use of text-to-speech (TTS) software as an accommodation for students with learning disabilities and its impact on improving reading comprehension. As the development and availability of TTS tools and assistive technologies have increased over the past decade, it is significant to explore how they are used to accommodate students at all levels of education to promote a universal design of learning. Based on a review of the current literature and utilizing self-regulated learning theory as a framework, four significant themes have emerged: (a) TTS being seen as a compensatory tool; (b) improving reading abilities and comprehension; (c) increasing student motivation and self-efficacy; and (d) the need for training for students, educators, and parents. Findings of this literature review revealed that overall, TTS software is commonly used as a compensatory tool (mainly at the postsecondary level), has assisted in students improving reading speed, fluency, and content retention, resulted in increased student self-efficacy in reading abilities and independent learning, and that there is a significant need to allocate training and technological resources to support students. As there are various directions for future research, exploring this area can contribute to schools promoting inclusive and accommodating learning environments.